A novel electrode of ternary CuNiPd nanoneedles decorated Ni foam and its catalytic activity toward NaBH4 electrooxidation. (10th March 2019) - Song, Congying; Wang, Guiling; Li, Biaopeng; Miao, Chenxu; Ma, Kaijing; Zhu, Kai; Cheng, Kui; Ye, Ke; Yan, Jun; Cao, Dianxue; Yin, Jinling
Abstract: Facile hydrothermal method and galvanic replacement are employed to synthesize an electrode of ternary CuNiPd nanoneedles decorated Ni foam toward NaBH4 electrooxidation. In the whole preparation, traditional polymer binders are avoided which efficiently lowers the electrode cost. X-ray diffraction, scanning electron microscopy and transmission electron microscopy are conducted to study the phase composition and morphology of CuNiPd nanoneedles. The unique needle-like structure of the as-prepared electrode allows electrolyte to fully contact with electrode surface which is beneficial to improve the catalytic activity. Besides, the electrochemical performance is tested through chronoamperometry and cyclic voltammetry in a traditional three-electrode system. In 2 mol L −1 NaOH and 0.3 mol L −1 NaBH4, a current density of 710 mA cm −2 at 0 V on the CuNiPd nanoneedles decorated Ni foam electrode is achieved which reveals a desired catalytic property for NaBH4 oxidation. In addition, the activation energy and number of exchange electrons of NaBH4 oxidation on CuNiPd nanoneedles decorated Ni foam electrode are 18.42 kJ mol −1 and 4.9. The excellent catalytic activity is a result of the synergy effect of Cu, Ni and Pd which makes the as-prepared electrode to be an alternative choice for direct sodium borohydride fuel cell.